Seaweed, Used as a Water-Retaining Agent, Improved the Water Distribution and Myofibrillar Protein Properties of Plant-Based Yak Meat Burgers Before and After Freeze–Thaw Cycles - Yujiao Wang; Xinyi Chang; Yingzhen Wang; Jiahao Xie; Ge Han; Hang Qi (Foods)
This study investigated quality changes in seaweed–yak patties before and after freeze–thaw by varying seaweed addition levels (10–70%). Macroscopically, the effects on water-holding capacity, textural properties, and oxidative indices of restructured yak patties were evaluated. Microscopically, the impact of seaweed-derived bioactive ingredients on patty microstructure and myofibrillar protein characteristics was examined. LF-NMR and MRI showed that 40% seaweed addition most effectively restricted water migration, reduced thawing loss, and preserved immobilized water content. Texture profile analysis (TPA) revealed that moderate seaweed levels (30–40%) enhanced springiness and minimized post-thaw hardness increases. SEM confirmed that algal polysaccharides formed a denser protective network around the muscle fibers. Lipid oxidation (MDA), free-radical measurements, and non-targeted metabolomics revealed a significant reduction in oxidative damage at 40% seaweed addition, correlating with increased total phenolic content. Protein analyses (particle size, zeta potential, hydrophobicity, and SDS-PAGE) demonstrated a cryoprotective effect of seaweed on myofibrillar proteins, reducing aggregation and denaturation. These findings suggest that approximately 40% seaweed addition can improve the physicochemical stability and antioxidant capacity of frozen seaweed–yak meat products. This work thus identifies the optimal seaweed addition level for enhancing freeze–thaw stability and functional quality, offering practical guidance for the development of healthier, high-value restructured meat products.